Homozygous knockout of eEF2K alleviates cognitive deficits in APP/PS1 Alzheimer’s disease model mice independent of brain amyloid β pathology - Kasica, Nicole P.; Zhou, Xueyan; Jester, Hannah M.; Holland, Caroline E.; Ryazanov, Alexey G.; Forshaw, Tom E.; Furdui, Cristina M.; Ma, Tao (Frontiers in Aging Neuroscience, 2022)
Maintenance of memory and synaptic plasticity depends on de novo protein synthesis and accumulating evidence implicates a role of dysregulated mRNA translation in cognitive impairments associated with Alzheimer’s disease (AD). Accumulating evidence demonstrates hyper-phosphorylation of translation factor eukaryotic elongation factor 2 (eEF2) in the hippocampi of human AD patients as well as transgenic AD model mice. Phosphorylation of eEF2 (at the Thr 56 site) by its only known kinase, eEF2K, leads to inhibition of general protein synthesis. A recent study suggests that Aβ-induced neurotoxicity could be associated with an interaction between eEF2 phosphorylation and the transcription factor nuclear erythroid 2-related factor (NRF2)-mediated antioxidant response. In this brief communication, we report that global homozygous knockout of the eEF2K gene alleviates deficits of long-term recognition and spatial learning in a mouse model of AD (APP/PS1). Moreover, eEF2K knockout does not alter brain Aβ pathology in APP/PS1 mice. The hippocampal NRF2 antioxidant response in the APP/PS1 mice, measured by expression levels of NQO1 and HO-1, is ameliorated by suppression of eEF2K signaling. Together, the findings may contribute to our understanding of the molecular mechanisms underlying AD pathogenesis, indicating that suppression of eEF2K activity could be a beneficial therapeutic option for this devastating neurodegenerative disease.